Investigation of Fin Spacing for Heat Transfer Enhancement in Cross Flow Over Tubes Between Two Parallel Plates - Ahmad Nurye Oumer; Amer Farhan Alias (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2019)
This research explains the investigation of fin spacing for heat transfer enhancement in the finned tube heat exchanger. The objective of this paper is to recommend the optimum fin spacing for heat transfer enhancement. Three different types of tube and spacing are identified through the simulation from Ansys software. The data between simulation using Ansys Fluent and published literature were being compared. Graph of total pressure, Nusselt number and total temperature have been plotted to make the comparison. Result obtained showed that were a bigger agreement between the simulation and published literature for both types of the tube which are circular and elliptic. From the analysis, there were considered two types of arrangement for the different types of tube. From that, the aligned arrangement is the best for heat transfer enhancement compared to the staggered. For the effect of spacing, there was three spacing which is 1.7 mm, 1.8 mm, and 2.0 mm spacing with velocity and the total heat flux is set to be constant (v =1.4 m/s; q = 500 W/m2). For the circular tube, it can be seen that the wider of the fin spacing gave the best heat transfer enhancement in the heat exchanger. Different from the circular which is 1.8 mm spacing is the best for heat transfer enhancement. Other types of tube are a flat surface which is comparing with the variations of Nu vs Re with different heat flux. Then, the result showed that as the Re is increased the Nu will also increase. In the other side, it is recommended for future work to do the real model dimension followed to import to the Ansys instead of assuming the model is symmetrical.